Seeking Internationalization: The State of Canadian Higher Education - Anderson, Tim (Canadian Journal of Higher Education, 2015)
This article explores the internationalization of Canadian universities, with a focus on the rise of foreign postsecondary students in Canada, the economic impacts, and the various benefits, challenges, and adjustments that have been influenced by the continuing demographic shifts on Canadian campuses since 2000. Rooted in recent global and Canadian higher education internationalization trends, this paper suggests that accommodations for such shifts have not kept pace with the influx of culturally and linguistically diverse foreign students, whose population growth rate outpaces domestic university students’ by several times. I conclude with unresolved dilemmas that continue to pose challenges for Canadian universities, and with suggestions for manageable supports to ensure the needs of students are responsibly balanced with the economic constraints of universities.